Persepsi Anggota Gereja Atas Pengendalian Internal - Eka Adhi Wibowo; Heru Kristanto (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2018)
Abstract This study aims at analyzing differences in perceptions of church members (pastors, treasurers, and congregations) on internal control and the relationship between the amount of offerings and the church’s perception of internal control. Respondents come from Protestant Christian churches in particular which are the supporting synods of Duta Wacana Christian University, Yogyakarta. They consist of 31 congregations with 92 people as respondents. The result of Kruskal Wallis statistic test shows that there is no difference of perception among the three members of the church about internal control. The Pearson correlation test results between the amount of offerings and the church member’s perception of financial control is positive, but very low. The development of the amount of offerings is followed by internal control, albeit at low levels. AbstrakPenelitian ini bertujuan untuk menganalisis perbedaan persepsi anggota gereja (pendeta, bendahara, dan jemaat) tentang pengendalian internal dan hubungan antara jumlah persembahan dengan persepsi gereja terhadap pengendalian internal. Responden berasal dari Gereja-gereja Kristen Protestan khususnya yang menjadi sinode gereja pendukung Universitas Kristen Duta Wacana, Yogyakarta, sebanyak 31 jemaat dengan 92 orang sebagai responden. Hasil uji statistik Kruskal Wallis tidak terdapat perbedaan persepsi di antara ketiga anggota gereja tentang pengendalian internal. Hasil uji statistik korelasi Pearson antara jumlah persembahan dengan persepsi anggota gereja terhadap pengendalian keuangan adalah positif, tetapi sangat rendah. Perkembangan jumlah persembahan diikuti pengendalian internal, meskipun dengan kadar rendah.